Evaluating the predictive significance of D-dimer in conjunction with CA724 for the postoperative outcomes in gastric cancer: A retrospective cohort analysis - Yuanzheng Zhao; Jiaqi Han; Rong Yang; Shuqin Wang; Xinran Zhao; Ziyuan Wang; Hongxia Lu (PLoS ONE, 2025)
Background Gastric cancer represents a highly aggressive form of malignant tumor originating from the epithelial cells lining the gastric mucosa. Despite notable improvements in treatment approaches over the last few years, the associated mortality rate continues to be considerably high. Therefore, there is a pressing requirement for dependable biomarkers that can be utilized to predict and monitor prognosis, as well as to formulate targeted treatment strategies for patient groups at high risk. Methods We conducted an analysis of data collected from patients who were diagnosed with gastric cancer and underwent radical gastrectomy at Shanxi Cancer Hospital from June 2017 to June 2018, with follow-up data gathered over a five-year duration until 2023. Patient follow-up information was sourced from the hospital’s monitoring system. The analysis focused on the variances in effectiveness of D-dimer against different tumor markers through Cox stratification analysis. The tumor marker that exhibited the most pronounced impact was selected to formulate a novel combined indicator. Furthermore, we examined how this combined indicator influences five-year overall survival (OS) outcomes following gastric cancer surgery using Cox multivariate regression analysis. Results The Cox multivariate regression analysis revealed that the effect value of the D_Dimer-CA724 Middle group on the overall survival rate post-surgery for gastric cancer was found to be 1.42 (1.13–1.78), p = 0.003 (<0.05), in comparison with the D_Dimer-CA724 Low group. For the D_Dimer-CA724 High group, the effect value on overall survival after gastric cancer surgery was 2.11 (1.65–2.68), p < 0.001. Additionally, the trend test results indicated a value of 1.46 (1.29–1.64) with p < 0.001, demonstrating statistical significance. When compared to the D_Dimer-CA724 Low group, both the D_Dimer-CA724 Middle and High groups showed markedly poorer prognoses, with increased risks of 42% and 111%, respectively, highlighting a highly significant finding in clinical practice. Conclusion The integrated measure of D-dimer and CA724, referred to as D-dimer_CA724, serves as an independent predictor for the postoperative outcomes of gastric cancer, demonstrating superior predictive capability compared to the individual markers. In clinical settings, patients with gastric cancer exhibiting elevated levels of D-dimer_CA724 tend to experience worse prognoses following surgery. This measure holds significant potential for widespread application and promotion within clinical practice.